Pengaruh Media Sosial terhadap Tingkat Pengetahuan dan Motivasi Orang Tua dalam Vaksinasi HPV pada Siswi Sekolah Dasar di Kabupaten Kediri Tahun 2025 - Nada Septika Windraswari; Dewi Setyowati; Indra Yuliati (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Objective: This study aims to analyze the influence of social media on the level of knowledge and motivation of parents in administering Human Papillomavirus (HPV) vaccination to elementary school students. Method: The study used a cross-sectional design. The population was all parents of elementary school students at Kediri Elementary School with a sample of 81 respondents selected using total sampling technique. The research variables included the use of social media as an independent variable and the level of knowledge and motivation of parents as dependent variables. Data were collected using a structured questionnaire and analyzed bivariately using the Chi-Square test. Results: The results showed that most respondents had a moderate to high level of social media use. There was a significant relationship between social media use and the level of parental knowledge (p = 0.004) and the level of parental motivation in administering HPV vaccination (p = 0.002). Conclusion: Social media has a significant effect on increasing parental knowledge and motivation in supporting HPV vaccination in elementary school students.